Teachers’ Perceptions of Utilizing Quizizz Application in ELT for Young Learners - Siti Handayani Harahap; Farida Repelita Waty Kembaren (Scope : Journal of English Language Teaching, 2023)
At the current, the usage of learning media is crucial in the sphere of education. Media integration has been used in the classroom by both students and teachers. To keep up with the digital shift in society, teachers must include technology in their lesson plans. For the instructor to establish an engaging teaching and learning process, using technology in the process becomes crucial and necessary. Quizizz has also developed into one of the web tools that instructors utilize in ELT classrooms. This study looks into how English teachers feel about utilizing Quizizz in their classes. A case study was chosen as the research design in this qualitative study. The researchers conducted semi-structured interviews with ten English teachers for prime schools in Medan and distributed the Likert scale questionnaire to get the data. This study found the perceptions of English teachers in utilizing the Quizizz application for young learners. The study investigated English teachers’ perceptions of the effectiveness, feasibility, the difficulty of utilizing Quizizz, how Quizizz can motivate the students, and the willingness of the teachers to continue using Quizizz in the English classroom. Briefly, the teachers perceive that Quizizz has benefits in teaching English even Quizizz has drawbacks too.